Characterization of calcium, phosphate and peroxide interactions in activation of mitochondrial swelling using derivative of the swelling curves - Drahota, Zdeněk; Endlicher, René; Staňková, Pavla; Rychtrmoc, David; Milerová, Marie; Cervinková, Zuzana (Journal of bioenergetics and biomembranes, 2012)
We describe a new method for the analysis of mitochondrial swelling curves. Using classical swelling curves, only the maximum extent of the swelling can be calculated in a numerical form. However, taking the derivative of the classical swelling curves enables the evaluation of two additional parameters of the swelling process in a numerical form, namely, the maximum swelling rate after the addition of the swelling inducer (as dA₅₂₀/10 s) and the time (in sec) at which the maximum swelling rate after the addition of the swelling inducer is obtained. The use of these three parameters enables the better characterization of the swelling process as demonstrated by the evaluation of calcium and phosphate interactions in the opening of the mitochondrial permeability transition pore and by the characterization of the peroxide potentiating action.
Keywords: permeabilita; Male; Rats; zduření mitochondrií; Intracellular Membranes; transportní proteiny mitochondriální membrány; vápník; potkani Wistar; Peroxides; Animals; jaterní mitochondrie; Calcium; Mitochondrial Swelling; Mitochondrial Membrane Transport Proteins; Mitochondrial Permeability Transition Pore; Mitochondria, Liver; zvířata; mužské pohlaví; Permeability; přechodový pór mitochondriální permeability; krysa rodu Rattus; Phosphates; fosfáty; Rats, Wistar; intracelulární membrány; peroxidy